Response Of Growth And Production Onion (Allium Ascalonicum L.) On Treatment Of Umbi Amount And Chicken Fertilizer - A Miftakhurrohmat; Yarra Arlyani Nilam Tikam (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to determine the response of growth and production of red onion (Allium ascalonicum L.) on the treatment of the number of tubers and chicken manure. This research was conducted at Green House Faculty of Agriculture University of Muham- madiyah Sidoarjo in May to July 2017. The design used factorial RAK and BNJ advanced test. The first factor is the number of tubers consists of 3 levels, namely the number of tubers per planting hole consisting of 1, 2 and 3, while the second factor is the dosage of chicken manure consisting of 3 levels ie 15 tons / ha, 20 tons / ha and 25 tons / ha. Based on the results of research conducted that there is a real interaction between the treatment of chicken manure dosage and the number of tubers per planting hole to vari- able number of tubers per hill, the number of tuber planting hole showed a significant effect on tuber weight and dry weight of tuber. The best treatment was chicken manure 20 ton / ha and 3 tuber per planting hole yielding plant length 43,94 cm, number of tiller per hill 18,00 tillers, number of tubers per hill 18,33 bulb, tuber dry weight 13,98 gr, wet weight of tuber 28,33 gr and tuber volume 26,67 ml.